Adaptive control by neural networks - Marzuki Khalid, 1959-2012; Julio Tanomaru; Sigeru Omatu, 1946-; JSPS-VCC Seminar on Integrated Engineering (3rd : 1990 : Universiti Malaya, K Lumpur) (Kuala Lumpur : Universiti Malaya, 1990)
57